2005
DOI: 10.1186/bcr1148
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of Wnt pathway genes in breast cancer

Abstract: There is compelling evidence from transgenic mouse studies and analysis of mutations in human carcinomas indicating that the TGF-β signal transduction pathway is tumor suppressive. We have shown that overexpression of TGF-β1 in mammary epithelial cells suppresses the development of carcinomas and that expression of a dominant negative type II TGF-β receptor (DNIIR) in mammary epithelial cells under control of the MMTV promoter/enhancer increases the incidence of mammary carcinomas. Studies of human tumors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…This pathway shows more activation at stage one, but there has been no report of the presence of Wnt signaling related protein in tumor cells [58]. The results of this study along with reported expression change for some of the mainly involved proteins in this pathway such as WNT10A and WNT6 show up-regulation [59][60][61][62], while WNT11 displays down-regulation which is at odds with Dwyer and colleagues' studies [63].…”
Section: Discussioncontrasting
confidence: 74%
“…This pathway shows more activation at stage one, but there has been no report of the presence of Wnt signaling related protein in tumor cells [58]. The results of this study along with reported expression change for some of the mainly involved proteins in this pathway such as WNT10A and WNT6 show up-regulation [59][60][61][62], while WNT11 displays down-regulation which is at odds with Dwyer and colleagues' studies [63].…”
Section: Discussioncontrasting
confidence: 74%